2019
DOI: 10.1002/jbm.b.34425
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of ageing resistant transparent nanocrystalline yttria‐stabilized zirconia implants

Abstract: The “Window to the Brain” is a transparent cranial implant under development, based on nanocrystalline yttria‐stabilized zirconia (nc‐YSZ) transparent ceramic material. Previous work has demonstrated the feasibility of this material to facilitate brain imaging over time, but the long‐term stability of the material over decades in the body is unknown. In this study, the low‐temperature degradation (LTD) of nc‐YSZ of 3, 6, and 8 mol % yttria is compared before and after accelerated ageing treatments following IS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…This claim would have been strengthened by comparison of the optical and mechanical properties of the implant before implantation and after 4 weeks in the body. However, these optical and mechanical comparisons were made in a prior study (Davoodzadeh et al, 2019 ) where we simulated the aging that the implants would undergo over many decades in the body using ISO standard methods for the aging stability of zirconia implants (i.e., autoclave processing at 134°C at a water partial pressure of 2–3 bar; ISO 13356:2008) (Deville et al, 2006 ; Chevalier et al, 2007 ). This study showed that the WttB implant has excellent stability against low temperature degradation and did not exhibit any crystallite phase change, nor change in optical transmittance or Vickers hardness due to these tests, making such changes very unlikely over the 4 weeks of this current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This claim would have been strengthened by comparison of the optical and mechanical properties of the implant before implantation and after 4 weeks in the body. However, these optical and mechanical comparisons were made in a prior study (Davoodzadeh et al, 2019 ) where we simulated the aging that the implants would undergo over many decades in the body using ISO standard methods for the aging stability of zirconia implants (i.e., autoclave processing at 134°C at a water partial pressure of 2–3 bar; ISO 13356:2008) (Deville et al, 2006 ; Chevalier et al, 2007 ). This study showed that the WttB implant has excellent stability against low temperature degradation and did not exhibit any crystallite phase change, nor change in optical transmittance or Vickers hardness due to these tests, making such changes very unlikely over the 4 weeks of this current study.…”
Section: Discussionmentioning
confidence: 99%
“…We previously introduced a potential solution (Castillo-Vega et al, 2012 ; Damestani et al, 2013 , 2016a , b ; Gutierrez et al, 2017 ; Davoodzadeh et al, 2018 , 2019 ; Cano-Velázquez et al, 2019 ) in the form of a transparent ceramic cranial implant called the Window to the Brain (WttB) implant. This implant is made of nanocrystalline Yttria-Stabilized Zirconia (nc-YSZ), which possesses the requisite mechanical strength (Davoodzadeh et al, 2019 ) and biocompatibility (Damestani et al, 2016b ) to serve as a permanent optical access window in human patients. In our previous work, we demonstrated the in vivo use of this WttB implant for Optical Coherence Tomography (OCT) imaging of the brain in mice (Damestani et al, 2013 ) as well as for repeated Laser Speckle Imaging (LSI) of mouse cerebral blood flow (Davoodzadeh et al, 2018 ) over 4 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…The application of transparent cranial implants holds the transformative potential for facilitating the diagnosis and treatment of a wide variety of brain pathologies and neurological disorders. We have recently reported the properties of our transparent nc-YSZ implant including an excellent ageing resistance evaluated through zirconia-based surgical implants ISO tests 43 . The biocompatibility of zirconia-based implants and the OCA (PG and PEG) have also been reported previously 53,54 .…”
Section: Discussionmentioning
confidence: 99%
“…Conventional cranial prosthesis including titanium, alumina, and acrylic 37 , have not provided the requisite combination of transparency and toughness required for clinically-viable transparent cranial implants. To address this challenge, our group has previously introduced a transparent nanocrystalline yttria-stabilized-zirconia cranial implant material, which possesses the mechanical strength and biocompatibility which are prerequisites for a clinically-viable permanent cranial implant for patients [24][25][26][27][38][39][40][41][42][43][44][45][46] . This implant has been referred to in the literature as the "Window to the Brain" (WttB) implant.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of Y 2 O 3 can stabilize the tetragonal and cubic crystal structure of ZrO 2 due to the presence of oxygen vacancies [1,2]. Yttria-stabilized ZrO 2 ceramics show many mechanical and functional advantages, such as high hardness (H), high chemical stability, low thermal conductivity, high oxygen diffusivity, and well-proven biocompatibility [3][4][5]. Cubic yttria-stabilized ZrO 2 (8 mol% yttria-stabilized zirconia (8YSZ)) transparent ceramics have a high refractive index (n) of ~2.2 [6,7], which is higher than those of most optical glasses and most oxide crystals.…”
Section: Introduction mentioning
confidence: 99%